2021
DOI: 10.1109/tnsre.2021.3105388
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biomechanical Assessment of a Novel Handle-Based Wheelchair Drive

Abstract: Push-rim wheelchair propulsion frequently causes severe upper limb injuries in people relying on the wheelchair for ambulation. To address this problem, we developed a novel handle-based wheelchair propulsion method that follows a cyclic motion within ergonomic joint ranges of motion. The aim of this study was to measure hand propulsion forces, joint excursions and net joint torques for this novel propulsion device and to compare its performance against traditional push-rim wheelchair propulsion. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… EL is a rotary joint 47 , 62 with one DOF rotating around the Z -axes (the composite joint structure contributes significantly to the stability of forearm motion). WR is a rotary joint 47 , 63 with two DOFs rotating around the X - and Z -axes (the composite joint structure contributes significantly to the sophisticated motions and stability of the palm). The clavicle is horizontal (parallel to the X–Z plane) when the arm is in its natural downward state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… EL is a rotary joint 47 , 62 with one DOF rotating around the Z -axes (the composite joint structure contributes significantly to the stability of forearm motion). WR is a rotary joint 47 , 63 with two DOFs rotating around the X - and Z -axes (the composite joint structure contributes significantly to the sophisticated motions and stability of the palm). The clavicle is horizontal (parallel to the X–Z plane) when the arm is in its natural downward state.…”
Section: Resultsmentioning
confidence: 99%
“…WR is a rotary joint 47 , 63 with two DOFs rotating around the X - and Z -axes (the composite joint structure contributes significantly to the sophisticated motions and stability of the palm).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the current findings indicate that propelling a wheelchair with this novel HBP device is more efficient and less strenuous than propelling a wheelchair with a pushrim. In addition, our previous study (23) showed that the HBP device may lower the probability of upper limb injuries by reducing joint loads and ergonomic joint ranges. To adapt to an individual user's wheelchair, the horizontal and vertical adjustment mechanisms shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Our group has developed a novel handle-based propulsion (HBP) mechanism for conventional wheelchairs as a compact indoor alternative to PRP (21). With an ergonomically optimized propulsion movement and the ability to continuously apply propulsive force, HBP offers a continuous cyclic motion at ergonomic joint ranges of motion and has been shown to decrease joint excursions and maximum joint torques during propulsion (21)(22)(23). The aim of the current study was to investigate differences in metabolic cost and mechanical efficiency for this novel HBP device compared with the standard PRP.…”
mentioning
confidence: 99%